2017
DOI: 10.1073/pnas.1708628114
|View full text |Cite
|
Sign up to set email alerts
|

Insights into functions of the H channel of cytochrome c oxidase from atomistic molecular dynamics simulations

Abstract: Proton pumping A-type cytochrome oxidase (CO) terminates the respiratory chains of mitochondria and many bacteria. Three possible proton transfer pathways (D, K, and H channels) have been identified based on structural, functional, and mutational data. Whereas the D channel provides the route for all pumped protons in bacterial A-type COs, studies of bovine mitochondrial CO have led to suggestions that its H channel instead provides this route. Here, we have studied H-channel function by performing atomistic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 77 publications
1
25
0
Order By: Relevance
“…However, mutations of the analogous H-channel residues in Rb. sphaeroides CcO [153] and yeast [154] did not support this assignment. Recent simulations with MCCE hydrogen bond network analysis in Rb.…”
Section: The P-side Exit Pathmentioning
confidence: 85%
“…However, mutations of the analogous H-channel residues in Rb. sphaeroides CcO [153] and yeast [154] did not support this assignment. Recent simulations with MCCE hydrogen bond network analysis in Rb.…”
Section: The P-side Exit Pathmentioning
confidence: 85%
“…In addition, several detailed models have been proposed for proton translocation via the Hchannel, such as those involving the changes in the redox state of heme a (Redox Bohr effect) (34,35) and proton accumulation mechanisms (1,14,36,37), although their role in proton translocation has been disputed (38). Recently, a detailed analysis of the H-channel by molecular dynamics simulations was reported by Sharma et al (39). It was concluded that proton translocation through the upper and central regions of the H-channel is possible, but it is restricted in the region near H413 because of the absence of a sufficient number of water molecules to mediate proton translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of translocating protons, it was proposed that the H-channel may serve as a dielectric well in which the dipoles of the polar residues are altered in response to redox state changes in heme a (39). However, Shimada et al (40) noted that a reanalysis of the simulations is needed, as in a more recent high-resolution structure (PDB ID code: 5B1A; resolution = 1.6 Å) additional waters were identified in the H413 region, which were not present in the lower-resolution structure (PDB ID code: 1V54; resolution = 1.8 Å) originally used by Sharma et al (39). Interestingly, the conformational changes in the farnesyl side chain of heme a and in Loop-I-II in bCcO were not observed in the bacterial enzyme (R. sphaeroides CcO) when the oxidized and reduced structures were compared (20), suggesting that the mechanism of proton translocation may not be conserved in mammalian and bacterial CcOs.…”
Section: Discussionmentioning
confidence: 99%
“…While NORs use exclusively heme b and bind iron (Fe B ) in their nonheme center with a conserved 3His-1Glu first coordination sphere, HCOs may host different types of hemes (e.g., heme o, a, and b) and bind copper (Cu B ) with a tripodal 3His coordination sphere, depending on the organism [73]. Thorough mechanistic studies have been performed for these two homologous classes of proteins [74][75][76][77][78][79] and few details are still under debate [80][81][82]. Nonetheless, in both cases protein matrix is able to promote selectivity of one metal over the other and to drive the correct inter-metal distance along the various oxidation states of the metal and reaction intermediates [83].…”
Section: Figmentioning
confidence: 99%